Understanding right-wing populism and what to do about it - Halikiopoulou, D; Vlandas, T (Friedrich Ebert Stiftung, 2022)
This report examines the electoral success of right-wing populist parties (RWPPs) in 17 European countries and makes recommendations for how progressives should respond. Specifically, we study the three Ps: People: Why do individual people vote for RWPPs? Policy: What is the role of policy? Parties: What makes certain RWPPs more successful than others? The structure of the Three Ps provides a framework to address crucial questions many progressive decision-makers, strategists and citizens have: Is it cultural or economic concerns that drive support for RWPPs? Can economic & social policies prevent the success of RWPPs? Can populism alone explain the success of RWPPs? What should progressives do to address voters of RWPPs?